Hsmar1 transposition is sensitive to the topology of the transposon donor and the target - Claeys Bouuaert, Corentin; Chalmers, Ronald (Public Library of Science, 2013)
Hsmar1 is a member of the Tc1-mariner superfamily of DNA transposons. These elements mobilize within the genome of their host by a cut-and-paste mechanism. We have exploited the in vitro reaction provided by Hsmar1 to investigate the effect of DNA supercoiling on transposon integration. We found that the topology of both the transposon and the target affect integration. Relaxed transposons have an integration defect that can be partially restored in the presence of elevated levels of negatively supercoiled target DNA. Negatively supercoiled DNA is a better target than nicked or positively supercoiled DNA, suggesting that underwinding of the DNA helix promotes target interactions. Like other Tc1-mariner elements, Hsmar1 integrates into 5′-TA dinucleotides. The direct vicinity of the target TA provides little sequence specificity for target interactions. However, transposition within a plasmid substrate was not random and some TA dinucleotides were targeted preferentially. The distribution of intramolecular target sites was not affected by DNA topology.